THE STATE AUTO DETERMINATION FROM EUROPE 1918: CZECHOSLOVAKIA’S INDEPENDENCE AND HER PLACE IN THE INTERNATIONAL SYSTEM - Roman, Alexandru (CEP USM, 2018)
The article referred to some consequences of the end of the First World War represented by the dissolution of the Austro-Hungarian Empire and the formation of new independent national states, among which was Czechoslovakia. In the territorial context, the Czechoslovakian state included the historical provinces Bohemia, Moravia and Silesia, to which Slovakia and Ruthenia were added, having in total a surface of 140 394 square km. On 14 November 1918, Tomáš Garrigue Masaryk had become the first president of the country officially called Czecho-Slovakian Republic (RČS) in 1918 – 1920 period, and as a simplified form, it was called Czecho-Slovakia. During the period 1920 – 1938, the country was named as Czechoslovakian Republic (ČSR), and the short name Czechoslovakia. Becoming a subject of international relations, the interwar Czechoslovakia played an important role in assuring the regional security in Europe. The Little Agreement, initiated by the minister of foreign affairs, Edvard Beneš, as organization of regional security, had quickened its activity by periodical convening of those 10 Conferences, etc.
Keywords: independent national states; international geopolitical disturbances